Preventive care for physical activity and fruit and vegetable consumption: a survey of family carer expectations of health service delivery for people with a mental health condition - Jacqueline M. Bailey; Tara L. Clinton-McHarg; Paula M. Wye; John H. Wiggers; Kate M. Bartlem; Jennifer A. Bowman (BMC, 2020)
Abstract Background Chronic disease is a leading cause of death globally, where inadequate fruit and vegetable consumption and inadequate physical activity are consistently implicated as key contributing risk factors for such diseases. People with a mental health condition are reported to experience a higher prevalence of such risks and experience an increased morbidity and mortality from resultant chronic disease. Despite guidelines identifying a need for services accessed by people with a mental health condition to provide care to address such health risk behaviours, sub-optimal care is frequently reported suggesting a need for innovative strategies to increase the provision of physical health care. An exploratory study was conducted to examine: 1) family carers' expectations of care provision regarding fruit and vegetable consumption and physical activity by health and community services for people with a mental health condition; 2) carer's own health risk behaviour status and perceptions of the influence of the health risk behaviours on mental health; and 3) possible associations of socio-demographic, clinical and attitudinal factors with carer expectations of care provision for fruit and vegetable consumption and physical activity. Methods Family carers (n = 144) of a person with a mental health condition completed a cross-sectional survey. Participants were members of a mental health carer support organisation operating in New South Wales, Australia. Results A high proportion of participants considered care for fruit and vegetable consumption and physical activity respectively should be provided by: mental health hospitals (78.5, 82.7%); community mental health services (76.7, 85.9%); general practice (81.1, 79.2%); and non-government organisations (56.2, 65.4%). Most participants perceived adequate fruit and vegetable consumption (55.9%), and physical activity (71.3%) would have a very positive impact on mental health. Carers who perceived adequate fruit and vegetable consumption and physical activity would have a positive impact on mental health were more likely to expect care for such behaviours from some services. Conclusions The majority of participants expected care for fruit and vegetable consumption and physical activity be provided by all services catering for people with a mental health condition, reinforcing the appropriateness for such services to provide physical health care for clients in a systematic manner.